I'll never tell [compact disc, unabridged] - McKenzie, Catherine (Brilliance Audio, Inc., 2019)
What happened to Amanda Holmes? Twenty years ago, she was found bludgeoned in a rowboat at the MacAllister family's Camp Macaw. No one was ever charged with the crime. Now, after their parents' sudden deaths, the MacAllister siblings return to camp to read the will and decide what to do with the prime real estate the camp occupies. But it's more complicated than a simple vote. The will stipulates that until they unravel the mystery of what happened to Amanda, they can't settle the estate. Any one of them could have done it, and each one is holding a piece of the truth. Will they work together to finally discover what happened to Amanda, or will their secrets finally tear the family apart?